Srategi Branding Melalui Inovasi Produk Dan Kemasan Minuman Herbal Instant UMKM Kendijati – CV. Ning Saudah - Septi Calista Nanda; Shaluna Mei Ardhana; IGN. Anom Maruta (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
MSMEs Ning Saudah is an instant herbal medicine product business located on Jalan Penjaringan Sari, Rungkut District, Surabaya. The owner of the business is named Nur Saudah. This research explores the role of product and packaging innovation in improving branding in Micro, Small and Medium Enterprises (MSMEs) in the instant herbal beverage sector, with a focus on the case study of MSME "Ning Saudah". Instant herbal drinks have great potential in the modern consumer market who is increasingly concerned about a healthy lifestyle. The challenges faced by MSMEs involve price competition, changes in consumer trends, and ambitions to expand market share. This research aims to analyze the influence of product and packaging innovation on increasing the branding of "Ning Saudah" MSMEs. The implementation method involves a two-month Merdeka Entrepreneurship (WMK) internship, with steps such as product analysis, research and development, production, packaging innovation, testing, marketing and evaluation. The research results show that through product and packaging innovation, "Ning Saudah" MSMEs succeeded in strengthening the attractiveness of the product and creating a strong brand image. A well-planned marketing and branding strategy also contributes to increasing product visibility. This internship program not only provides benefits for MSMEs in overcoming challenges, but also provides valuable experience for students.